Incidence of acute hamstring injuries in soccer: A systematic review of 13 studies involving more than 3800 athletes with 2 million sport exposure hours - Diemer, W. M.; Winters, M.; Tol, J. L.; Pas, H. I. M. F. L.; Moen, M. H. (Journal of Orthopaedic & Sports Physical Therapy, 2020)
Objective: To estimate the incidence and recurrence rate of acute hamstring injuries in all levels of soccer.